DNA release from plant tissue using focused ultrasound extraction (FUSE). (28th January 2023) - Stettinius, Alexia; Holmes, Hal; Zhang, Qian; Mehochko, Isabelle; Winters, Misa; Hutchison, Ruby; Maxwell, Adam; Holliday, Jason; Vlaisavljevich, Eli
Abstract: Premise: Sample preparation in genomics is a critical step that is often overlooked in molecular workflows and impacts the success of downstream genetic applications. This study explores the use of a recently developed focused ultrasound extraction (FUSE) technique to enable the rapid release of DNA from plant tissues for genetic analysis. Methods: FUSE generates a dense acoustic cavitation bubble cloud that pulverizes targeted tissue into acellular debris. This technique was applied to leaf samples of American chestnut ( Castanea dentata ), tulip poplar ( Liriodendron tulipifera ), red maple ( Acer rubrum ), and chestnut oak ( Quercus montana ). Results: We observed that FUSE can extract high quantities of DNA in 9–15 min, compared to the 30 min required for control DNA extraction methods. FUSE extracted DNA quantities of 24.33 ± 6.51 ng/mg and 35.32 ± 9.21 ng/mg from American chestnut and red maple, respectively, while control methods yielded 6.22 ± 0.87 ng/mg and 11.51 ± 1.95 ng/mg, respectively. The quality of the DNA released by FUSE allowed for successful amplification and next‐generation sequencing. Discussion: These results indicate that FUSE can improve DNA extraction efficiency for leaf tissues. Continued development of this technology aims to adapt to field‐deployable systems to increase the cataloging of genetic biodiversity, particularly in low‐resource biodiversity hotspots.